Die archäologischen Ausgrabungen in ‘Apunirereha’ und ‘Ria’ auf der Insel Malaita, Salomonen - Moser, Johannes; Kiko, Lawrence (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The archaeological research project done in Are’are since 2011 has been the first to be done in the area. The project is made through the cooperation between the Ministry of Culture and Tourism and the German Archaeological Institute, Commission for Archaeology of Non-European Cultures through Johannes Moser. Mr. John Tahinao the Director for Culture then is very instrumental in supporting the project and he was the person who suggested that the project must be done in his area. There is no doubt that being a trained Archaeologist at the University of Papua New Guinea he already knew that there is a potential of lithic site in his area. Mr. Tahinao has continuously appreciated every single progress of the project and in one of his respond he said the following words ‘The project is now gaining momentum’. The statement shows that the project has been successfully appreciated by the people, whom the project has been done, and the Ministry of Culture and Tourism in Honiara.